Preparation of the Serotonin Transporter PET Radiotracer 2-({2-[(Dimethylamino)methyl]phenyl}thio)-5-[18F]fluoroaniline (4-[18F]ADAM): Probing Synthetic and Radiosynthetic Methods - Milicevic Sephton, Selena; Zhou, Xiaoyun; Thompson, Stephen; Aigbirhio, Franklin I. (Synthesis, 2019)
Serotonin transporters (SERTs) are involved in regulating the concentration of synaptic serotonin and present a good target for many neurologic and psychiatric disorder drugs. Positron-emission tomography (PET) is a valuable tool in both diagnosis and monitoring treatment therapies, and hence much effort is being given to developing suitable PET agents for imaging SERT. Our interest in applying the fluorine-18 analogue 4-[18F]ADAM for imaging SERT prompted the development of an improved synthetic route to access unlabelled ADAM. This is achieved using Pd-catalysed coupling with thiosalicylic acid and an EDC/HOBt amide coupling in 36% yield over 4 steps. A novel radiolabelling precursor, the pinacol-derived boronic ester, is prepared from the bromide using the Miyaura borylation and is obtained in 27% yield over 6 steps. Pinacolate is then used for the radiolabelling of 4-[18F]ADAM based on Cu-mediated nucleophilic fluorination in which the presence of oxygen is critical for the reaction. A 1:1 substrate to copper ratio is found to be optimal when the reaction is performed in dimethylacetamide at 85 °C. Using these conditions, 4-[18F]ADAM is prepared in 29 ± 10% (n = 6) radiochemical conversion after hydrolysis of the Boc group with HCl. Furthermore, the method is successfully automated to afford 4-[18F]ADAM in 10% radiochemical conversion.
Keywords: 4-[18F]ADAM; serotonin transporter; copper-mediated fluorination; 18F-radiolabelling; PET imaging